The Stability Evaluation of Shaft during Drastic Drawdown Dewatering of Alluvium. (30th October 2019) - Du, Mingze; Xu, Yanchun; Duan, Heng; Li, Wen
Abstract : The hydrophobicity of the aquifer at the bottom of the porous alluvium will affect the stability of the shaft. According to the changes of water level and the compressive amount of alluvium, we can evaluate the shaft stability and predict the shaft failure. In this work, the simulation model of the auxiliary shaft in the Zhuxianzhuang Coal Mine is generated by using the Nsdc software to evaluate the stability of the shaft during drastic drawdown dewatering. Based on the measured hydrophobic compression ratio in an adjacent coal mine, the compressive amounts of the strata near the main and auxiliary shafts in the Zhuxianzhuang Coal Mine are predicted under the condition of drastic drawdown dewatering, which will be 249.69 mm and 302.75 mm, respectively. It is more likely that the shaft wall may fracture in the 15th day (fourth load level) under the condition of drastic drawdown dewatering. The formation compressive amount near the auxiliary shaft is approximately 320 mm, which is close to the measured predicted value. At the same time, the Fisher discriminant model is established, and it is predicted that the state of the main and auxiliary shafts will be failure under the conditions of drastic drawdown dewatering in the Zhuxianzhuang Coal Mine. Based on the simulating results, the technical means of using the ground grouting for early prevention and control is proposed.